Electronic properties and optical absorption of rectangular β12-borophene quantum dot - Feixia Liang; Jiayi Chen; Haiqing Xie; Qiang Wang; Lipeng Hou (AIP Advances)
Using the tight-binding model, we studied the electronic and optical properties of rectangular β12-borophene quantum dot (RBQD). We considered the effects of different lengths and widths on the energy levels and optical spectra of RBQD. As the RBQD size increases, the number of energy levels increases, with two sets of degenerate energy levels (E1 and E2) present. The degeneracy of the energy levels is closely related to the width of the RBQD but not to its length. In addition, multiple energy platforms have been formed. These degenerate levels and platforms significantly influence the optical absorption spectra, with energy level E2 playing an important role. Along the x-axis, the optical absorption spectrum undergoes a redshift with increasing length and exhibits a blueshift as the width increases. The y-axis spectrum exhibits a stable peak at E = 3.83 eV due to energy levels E1 and E2. This research on RBQD provides theoretical guidance for its application in optoelectronic devices, catalysis, sensing, long-term tracking, and bioimaging applications.